A cross-sectional study on the knowledge, attitude and practice of ICU nurses to ICU acquired weakness in grade-A tertiary hospitals in Beijing (北京市三甲医院ICU护士对ICU获得性衰弱的知信行现况调查及影响因素分析) - KUANG Lu (旷璐); SHAO Xin (邵欣) (中西医结合护理)
Objective To investigate the status quo of knowledge, belief and practice of ICU nurses with ICU acquired weakness (ICU-AW) and analyze its influencing factors, to provide a theoretical basis for the further development of evidence-based nursing practice to prevent ICU-AW. Methods A total of 210 ICU nurses from 8 grade-A tertiary hospitals in Beijing were selected by cluster sampling, and a self-designed questionnaire was used to survey them. Results The scores of knowledge, attitude and practice of ICU nurses were (5. 21+-2. 03), (28. 64 +-4. 12) and (26. 06+- 7. 23) respectively. The results of multiple stepwise regression analysis showed that the influencing factors of knowledge about ICU-AW were professional titles and the educational level(R2=0. 062, △R2=0. 117); The influencing factors of attitude towards ICU-AW was self-evaluation of the degree of mastery of knowledge related to ICU-AW (R2=0. 062, △R2=0. 117); The influencing factors of practice of ICU-AW was working years (R2=0. 061, △R2=0. 102). Conclusion ICU nurses have a positive attitude towards the clinical intervention of acquired weakness in ICU, but their knowledge and practice level are low. It is necessary to carry out systematic training of ICU acquired weakness knowledge for ICU nurses at different levels so as to improve their knowledge and behavior level and promote the early development of rehabilitation activities for ICU acquired weakness in clinical work, improve patient health outcomes. (目的 了解重症医学科(ICU)护士对ICU获得性衰弱的知识、信念、行为现状并分析其影响因素, 为科室下一步开展预防ICU-AW的循证护理实践提供理论依据。方法 于2023年11月采用整群抽样法抽取北京市8所三级甲等医院的210名ICU护士作为调查对象, 采用自编的ICU获得性衰弱知信行调查问卷对其进行问卷调查。结果 ICU 护士ICU 获得性衰弱知识、态度、行为得分分别为(5. 21+-2. 03)分、(28. 64+-4. 12)分和(26. 06+-7. 23)分。多元逐步回归分析结果显示, ICU 护士ICU 获得性衰弱知识的影响因素为职称和学历(R2=0. 186, △R2=0. 178); ICU获得性衰弱态度的影响因素为对ICU获得性衰弱相关知识掌握程度的自我评价(R2=0. 062, △R2=0. 117); ICU获得性衰弱行为的影响因素是工作年限(R2=0. 061, △R2=0. 102)。结论 ICU护士对于ICU获得性衰弱的临床干预态度较为积极, 但相关知识掌握程度及行为水平偏低。应该分层级对ICU护士进行ICU获得性衰弱相关知识的系统培训, 提高临床护士的知识及行为水平, 促进临床工作中针对ICU获得性衰弱相关康复活动的早期开展, 改善患者健康结局。)